Business model innovation of advertising operation based on RBM deep neural network - Li, You (Applied mathematics and nonlinear sciences, 2024)
RBM, as an important structural component unit in the mainstream model of deep learning, is being widely used in various fields. The article first discusses the RBM deep neural network algorithm, gives an overview of the related function algorithm combining RBM and neural network, and then proposes a deep network method oriented to the prediction of advertisement click rate. At the end of the article, the algorithm proposed in this paper is compared with the model performance test. An advertising company is used as an object of empirical research to analyze the change in its market share and turnover in the years 2022-2023. Explore the significance and role of RBM-based deep neural networks in the innovation of advertising business models.